Differential alterations in mitochondrial function induced by a choline-deficient diet: Understanding fatty liver disease progression - Teodoro, João S. (2008)
http://www.sciencedirect.com/science/article/B6W8G-4T72WXD-1/2/734055ec11eadc8100fee13e06c683d5